Analisis Temperature Humidity Index (THI) terhadap Kenyamanan Termal dengan Penambahan Tumbuhan Hijau pada Gedung Bertingkat - Harmin, Amalia; Isra, Muhammad; Fauzan, Fauzan; Bravikawati, Marini; Naziah, Afrahun; Kasim, Bukhari (Malikussaleh Journal of Mechanical Science and Technology, 2025)
Aceh Province is experiencing rapid changes in infrastructure along with population growth and globalization and urbanization. This development and growth has led to a significant increase in the construction of high-rise buildings in urban areas. In multi-storey buildings, the use of materials that have a low albedo against solar radiation, so that a lot of radiation is absorbed and stored in the form of heat in the building so that it can increase the temperature of the building up to 12 °C. The absence of heat absorbers such as green plants around the building affects the thermal comfort of building occupants. Thermal comfort can be measured using various parameters, one of which is the Temperature Humidity Index (THI). The use of green plants of the type of Sansevieria Ttrifasciata which is used as a building envelope for 7 days on the 2nd floor of the Samudra University Laboratory building to measure the temperature difference after being absorbed first by the (Sansevieria Ttrifasciata) in the photosynthesis process. The results show that the THI thermal comfort index is reached at 25°C to 26°C with the conditions shown based on the ASHRAE 55 standard is thermally comfortable.